Colostrum: The Golden Elixir of Health – Unveiling Its Multifaceted Benefits in Modern Medicine - Martyna Michalska; Karolina Winiarek; Wiktor Wardyn; Elżbieta Tokarczyk; Daria Ziemińska; Cezary Guzowski; Rafał Burczyk; Joanna Murawska (Quality in Sport)
Introduction: Colostrum is uniquely rich in immunoglobulins, growth factors, antibacterial peptides, probiotics, prebiotics, and essential vitamins and minerals. Available as a supplement, BC is used to prevent gastrointestinal infections, boost immune support, and aid in managing chronic inflammation, autoimmune diseases, and even athletic recovery.